2015
DOI: 10.1371/journal.pcbi.1004628
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Complexity of Auditory Receptive Fields

Abstract: Encoding properties of sensory neurons are commonly modeled using linear finite impulse response (FIR) filters. For the auditory system, the FIR filter is instantiated in the spectro-temporal receptive field (STRF), often in the framework of the generalized linear model. Despite widespread use of the FIR STRF, numerous formulations for linear filters are possible that require many fewer parameters, potentially permitting more efficient and accurate model estimates. To explore these alternative STRF architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(118 citation statements)
references
References 75 publications
(198 reference statements)
2
116
0
Order By: Relevance
“…Recent work [67] indicates that choosing different nonlinear output functions from a wide range of plausible candidates has only modest effects on the ability of LN models to capture neural response properties. We therefore did not attempt to systematically explore different types of output nonlinearity or to make the choice of nonlinearity as physiological as possible, but rather focused on an output nonlinearity that is simple, well characterized and widely used in the artificial network literature.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work [67] indicates that choosing different nonlinear output functions from a wide range of plausible candidates has only modest effects on the ability of LN models to capture neural response properties. We therefore did not attempt to systematically explore different types of output nonlinearity or to make the choice of nonlinearity as physiological as possible, but rather focused on an output nonlinearity that is simple, well characterized and widely used in the artificial network literature.…”
Section: Methodsmentioning
confidence: 99%
“…We additionally use a low-rank regularization penalty, that encourages approximately spatiotemporally separable filters [47, 48], a property that is common to receptive fields in a wide variety of sensory systems. In order to fit these models, we use methods based on proximal consensus algorithms (described in Methods).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the filter was applied in two stages: multiplication by an 18x3 spectral weighting matrix followed by convolution with a 3x15 temporal filter. Previous work has shown that this strategy is advantageous (Thorson, Liénard, and David 2015).…”
Section: Modeling Frameworkmentioning
confidence: 99%
“…The filterbank included C = 18 filters with f i spaced logarithmically from f low = 200 to f high = 20, 000 Hz. After filtering, the signal was smoothed and down-sampled to 100 Hz to match the temporal bin size of the PSTH, and log compression was applied to account for the action of the cochlea (Thorson, Liénard, and David 2015).…”
Section: Modeling Frameworkmentioning
confidence: 99%